Social Work in Suits: A Case Study on the Corporate Social Responsibility (CSR) Initiatives of Widus Foundation, Inc. (WFI) - Paola Ellaine D.Luzon; Jennifer Mae I.Milan; Eunice M.Noveno (Asean Social Work Journal, 2022)
The interconnectedness of corporate social responsibility (CSR) and social work has been established in past studies. However, there is still a lack of participation of social workers in the CSR field. This study aimed to describe and analyze the CSR initiatives of Widus Foundation, Inc. (WFI), a CSR company in the Philippines whose foundation manager is a social worker. A case study was done on the CSR program delivery of the WFI by collecting data through an online interview and questionnaire with the WFI foundation manager. Thematic analysis was used to analyze online interviews with WFI volunteers and beneficiaries to determine CSR best practices of the WFI. Findings showed that the CSR framework used by the WFI focuses on being inclusive, impact-driven, sustainable, and innovative or unique. Moreover, CSR best practices of the WFI that emerged from interviews with stakeholders were: (1) inclusive, (2) sustainable, (3) impactful, and (4) good administration. Results of this study can be used to establish the importance of social workers in the CSR field. The best practices identified can also serve as a starting point to establish standards in CSR delivery. Future studies may also be done on a wider scale involving several CSR companies.